THE EFFECT OF COMMUNICATION, SUPERVISION AND FACILITIES ON TEACHER JOB SATISFACTION IN MAJOR SUTOYO SM. COLLEGE FOUNDATION - Cahaya Adhan Dini; Emi Wakhyuni; Nashrudin Setiawan (International Journal of Management, Economic and Accounting, 2024)
This test study aims to find out whether communication has a significant effect on the performance of educators at the Major Sutoyo SM Teaching Foundation. Does supervision affect the performance of educators at the Major Sutoyo SM College Foundation. Does the office affect the performance of educators at the Major Sutoyo SM Teaching Foundation. The data testing procedure used is a quantitative research strategy with multiple linear regression analysis (SEM) and using the SmartPLS application. This study uses multiple linear regression. The sample in this study is 60 respondents. Primary data collection uses questionnaires. The results of the study showed that communication had an effect on the performance of educators at the Major Sutoyo SM College Foundation, where the t-data value was 4.697 > the table T was 1.96 and the p value was 0.010 < 0.05. Management has an effect on the fulfillment of the work of instructors at the Major Sutoyo SM Teaching Foundation, where the t-size value is 4.632 > T table 1.96 and the p value is 0.020 < 0.05. The position has a significant effect on the fulfillment of the work of instructors at the Major Sutoyo SM Teaching Foundation, where the t-size value is 4.371 > the T table is 1.96 and the p value is 0.030 < 0.05.